2017
DOI: 10.14740/jocmr2033w
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Respiratory Volume Monitor to Assess Respiratory Competence in Cardiac Surgery Patients After Extubation

Abstract: BackgroundPatients who have undergone cardiac surgery are generally mechanically ventilated postoperatively. Early postoperative extubation is currently recommended in anesthesia guidelines. No current technology can accurately, non-invasively, measure respiratory competence after extubation. Pulse oximetry has been helpful, but this is a late indicator of respiratory compromise. A novel, non-invasive, respiratory volume monitor (RVM) has been shown to deliver accurate continuous, real-time minute ventilation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This was later confirmed in the pediatric population, where respiratory volume monitor and spirometer measurements were also similar within a 10% error [ 15 ]. Also, in intubated patients, measurements correlated well with ventilator settings in cardiac surgery as well as in obese subjects [ 16 , 17 ]. This makes the monitor well suited to detect early changes in respiration before oxygenation is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…This was later confirmed in the pediatric population, where respiratory volume monitor and spirometer measurements were also similar within a 10% error [ 15 ]. Also, in intubated patients, measurements correlated well with ventilator settings in cardiac surgery as well as in obese subjects [ 16 , 17 ]. This makes the monitor well suited to detect early changes in respiration before oxygenation is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of RVM after extubation in postoperative patients has also been evaluated. Ianchulev et al 53 noted that RVM was able to provide clinicians with comprehensive, quantitative information related to breathing pattern and trends in ventilation that are not available with other technology at the time of their study. 53 The authors concluded that RVM shows real promise in improving patient safety in postextubation patients, among others.…”
Section: Noninvasive Minute Ventilation Monitoringmentioning
confidence: 99%
“…Ianchulev et al 53 noted that RVM was able to provide clinicians with comprehensive, quantitative information related to breathing pattern and trends in ventilation that are not available with other technology at the time of their study. 53 The authors concluded that RVM shows real promise in improving patient safety in postextubation patients, among others. Other tools with the ability to monitor postextubation respiratory status, like the integrated pulmonary index, 54 have been evaluated since the study by Ianchulev et al, 53 but to our knowledge they have not been compared directly.…”
Section: Noninvasive Minute Ventilation Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, with the invention of stethoscope, simple acoustical methods of respiratory assessment became available to the clinical community. With the subsequent invention of electronic amplification, a variety of new technologies became available, including respiratory monitoring belts placed on the chest and abdomen [6 -9], nasal pressure methods [10,11], nasal / oral thermistor methods [12,13] (the thermistor warms up with expired gases), nasal / oral capnography [14,15], extraction of respiratory information from the photoplethysmograph signal [16,17], and electrical impedance methods based on a small injected electrical current [18,19].…”
Section: Introductionmentioning
confidence: 99%